1974
DOI: 10.1159/000175540
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Converting Food Iron into Hemoglobin by the Anemic Rat

Abstract: The bioavailability of iron in dried whole egg, ground beef, whole-wheat flour, enriched flour and FeSO4 was evaluated in terms of hemoglobin regeneration. Sixty weanling male rats were made anemic by feeding a semi-purified basal diet containing 7.8 p.p.m. iron. They were divided into six groups to be fed the basal diet or the basal diet substituted with appropriate amounts of each iron source for 3 weeks. It was calculated that the milligrams of iron converted to hemoglobin per 100 mg of iron cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
1
1

Year Published

1976
1976
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 7 publications
3
51
1
1
Order By: Relevance
“…Such assays are subject to variations in amounts of iron consumed as affected by dietary iron content and/or diet acceptability (9). Differences in dietary iron content, iron quality and acceptability result in different growth responses (1 -4 , 9).…”
mentioning
confidence: 99%
“…Such assays are subject to variations in amounts of iron consumed as affected by dietary iron content and/or diet acceptability (9). Differences in dietary iron content, iron quality and acceptability result in different growth responses (1 -4 , 9).…”
mentioning
confidence: 99%
“…When the animals were given a single-labelled meal absorption was greater, as was found with the potato study, and the wheat: FeSO, value was 0.77. Mahoney et al (1974) showed that the efficiency of converting wheat Fe into haem-Fe in young, anaemic rats was two-thirds that of ferrous ascorbate. These results using rats compare well with results from normal human subjects in which Fe absorption from intrinsically-labelled wheat was two-thirds that from ferrous ascorbate (Hussain et al 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Hb-Fe pool (mg) = [body weight (g) x Hb (g L -1 ) x 6.7 x 0.335] /10,000 (1) Hb regeneration efficiency and relative biological value were estimated according to Mahoney et al (1974) (Equations 2 and 3):…”
Section: Methodsmentioning
confidence: 99%